2008
DOI: 10.1590/s0102-311x2008000800012
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos idosos residentes em dois municípios pobres das regiões Norte e Nordeste do Brasil: resultados de estudo transversal de base populacional

Abstract: This study aimed to determine the profile of the elderly population (≥ 60 years)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 15 publications
3
12
2
18
Order By: Relevance
“…The other ten studies analyzed vaccine coverage among the senior population. The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other ten studies analyzed vaccine coverage among the senior population. The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of them were surveys conducted in representative samples of the target population, 7,9,13,16,17,20,24 and the remaining three among outpatients of a primary care clinic and reference hospitals 22,23,30 . Five surveys detected vaccine coverage similar to the Ministry of Health's (MOH) administrative data 9,13,16,17,30 . On the other hand, large differences were observed by the other three: among the elderly of two low income communities ("favelas") in the city of Rio de Janeiro, survey coverage was 50.2% and 38.3%, compared to MOH 75.7% coverage for the whole city; 66.3% coverage in Belo Horizonte, the country's third largest city, compared to 85.5% according to MOH data; and 83.8% among outpatients of a primary care clinic in Botucatu, state of São Paulo, compared to 62.2% (MOH) 7,22,24 .…”
Section: Resultsmentioning
confidence: 99%
“…It is an 11-question measure that tests five areas of cognitive function: orientation, immediate memory, attention/concentration, delayed recall, language. Any score greater from regional differences, which evoke problems and hypotheses that need more investigation 3,4 . Populational studies with elderly require further consistent data about communication disorders and their impact on the health of this population [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The data on education and income demonstrate the low socioeconomic status of the sample. In addition, in the riverside setting analyzed, it seems possible to suggest that the elderly also function as income generators for their families, as in the population base study with poor elderly conducted by Cesar et al (2008). We observed that although considered low, the rural retirement benefi t received by the elderly participants has improved the purchasing power of the elderly, who have been able to invest in durable consumer goods for their homes, among other material and housing resources.…”
Section: Discussionmentioning
confidence: 71%
“…Concerning these studied domains, Cesar et al (2008) highlight the fact that most studies that involve the elderly do not describe their housing conditions, as though they were not a major determinant to their wellbeing and health status.…”
Section: Discussionmentioning
confidence: 99%